Functional characterization and immunogenicity of a novel vaccine candidate against tick-borne encephalitis virus based on Leishmania-derived virus-like particles - Zimna, Marta; Brzuska, Gabriela; Salát, Jiří; Svoboda, Pavel; Baranska, Klaudia; Szewczyk, Boguslaw; Růžek, Daniel; Krol, Ewelina (Antiviral research, 2023)
Tick-borne encephalitis virus (TBEV) is a major cause of neurological infections in many regions of central, eastern and northern Europe and northern Asia. In approximately 15% of cases, TBEV infections lead to the development of severe encephalitis or meningitis. The main route of TBEV transmission is tick bites; however, ingestion of dairy products from infected animals (goats, cattle and sheep) is also a frequent cause of the disease. Therefore, vaccination of livestock in virus endemic regions could also contribute to the decrease in TBEV infection among humans. Although few vaccines against TBEV based on inactivated viruses are available for humans, due to high costs, vaccination is not mandatory in most of the affected countries. Moreover, there is still no vaccine for veterinary use. Here, we present a characterization and immunogenicity study of a new potential TBEV vaccine based on virus-like particles (VLPs) produced in Leishmania tarentolae cells. VLPs, which mimic native viral particles but do not contain genetic material, show good immunogenic potential. For the first time, we showed that the protozoan L. tarentolae expression system can be successfully used for the production of TBEV virus-like particles with highly efficient production. We confirmed that TBEV recombinant structural proteins (prM/M and E) from VLPs are highly recognized by neutralizing antibodies in in vitro analyses. Therefore, VLPs in combination with AddaVax adjuvant were used in immunization studies in a mouse model. VLPs proved to be highly immunogenic and induced the production of high levels of neutralizing antibodies. In a challenge experiment, immunization with VLPs provided full protection from lethal TBE in mice. Thus, we suggest that Leishmania-derived VLPs may be a good candidate for a safe alternative human vaccine with high efficiency of production. Moreover, this potential vaccine candidate may constitute a low-cost candidate for veterinary use.
Keywords: Cattle; Animals; skot; Viral Vaccines; ovce; lidé; virové vakcíny; neutralizující protilátky; Mice; viry klíšťové encefalitidy; myši; protilátky virové; Encephalitis Viruses, Tick-Borne; Tick-borne encephalitis virus; Leishmania tarentolae; Antibodies, Neutralizing; Sheep; Leishmania; Encephalitis, Tick-Borne; Virus-like particles; zvířata; klíšťová encefalitida; Antibodies, Viral; Vaccine; Humans